2006
DOI: 10.1088/0953-8984/18/19/001
|View full text |Cite
|
Sign up to set email alerts
|

Nonsingular walls in plane cholesteric layers

Abstract: The structure of a straight interface (wall) between regions with differing values of the pitch in planar cholesteric layers with finite strength of the surface anchoring is investigated theoretically. It is found that the shape and strength of the anchoring potential influences essentially the structure of the wall and a motionless wall between thermodynamically stable regions without a singularity in the director distribution in the layer can exist for sufficiently weak anchoring only. More specifically, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…Quite recently another phenomena connected to the shape of the anchoring potential were studied. These are the temporal dynamics of the pitch jump [2,10] and the motion of a non-singular wall dividing the areas of different values of the pitch in a planar CLC layer [11,12,13]. These studies revealed also the dependence of the temporal evolution of the jump on the shape and the strength of anchoring for a relatively weak surface anchoring.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Quite recently another phenomena connected to the shape of the anchoring potential were studied. These are the temporal dynamics of the pitch jump [2,10] and the motion of a non-singular wall dividing the areas of different values of the pitch in a planar CLC layer [11,12,13]. These studies revealed also the dependence of the temporal evolution of the jump on the shape and the strength of anchoring for a relatively weak surface anchoring.…”
Section: Introductionmentioning
confidence: 89%
“…It happens that at If the described jump happens in a limited area of the layer surface the director distribution over the layer surface become inhomogeneous and the wall (interface between the configurations with N and N þ 1 half-turns of the director) occurs. Typically [12] the wall thickness Cano-Grandjean Wedge at Weak Anchoring 267 along the layer surface is much less than the layer thickness. The wall begins its motion in the direction of the N configuration, because the free energy of the N configuration per a unit layer area is higher than the corresponding value for the N þ 1 configuration [11,12].…”
Section: Plane Layermentioning
confidence: 99%
See 1 more Smart Citation
“…if the director at the surface coincides with the easy direction. Recently, however, Belyakov et al [3][4][5] proposed an alternative form for a weak anchoring energy density that is particularly relevant to twist geometries. In our notation, this alternative version may be written as…”
Section: Introductionmentioning
confidence: 99%
“…The physical motivation for the B form of surface energy is largely driven by pitch 'jumps' in cholesteric liquid crystals where the twist of the director is dominant and is related to the twist elastic constant K 2 [3][4][5]. By considering simple series expansions, it can be shown that the RP and B energies almost coincide when the actual surface twist angle is close to the easy direction / Ã .…”
Section: Introductionmentioning
confidence: 99%